Tysk som tillægskompetence – lærendes motivation, behov og erfaringer - Mirjam Gebauer; Aase Voldgaard Larsen; Anne Grethe Julius Pedersen; Simon Holleufer; Ida Vejnø (Globe)
This study explores how L2 learners of German as an Additional Competence (GAC) reflect on motivation, needs, expectations, experiences, and persistence. GAC is a new initiative that was launched in 2022 at Aalborg University, supported by a special budget from the Danish Ministry of Education and Research for boosting German and French language skills in higher education in Denmark. At Aalborg University, GAC is offered as courses outside of the academic curricula and ECTS system. To evaluate and further develop this new initiative, we have conducted 14 semi-structured interviews with course participants to inquire about their motivation, needs, expectations, and experiences. Theoretically and methodologically, the study is based on Dörnyei’s (2005) model of Motivational Self System in second language (L2) acquisition, the concept of target needs by Hutchinson and Waters (1987), Unger’s (2022) study of narrative constructions of needs in foreign language teaching, and Tinto’s (2020) concept of persistence, involving self-efficacy, sense of belonging, and perception of curriculum. The study provides insights into a broad variety of motivational factors, needs, persistence, and experiences from both previous German language learning and the GAC-courses. The findings of the study point towards both career-strategic and personal goals as key factors for the motivation of the participants. Moreover, their perceived needs focus on the enhancement of practical language skills. Accordingly, most participants expect the courses to allow for extensive training and practical exercises. Also, an informal and safe atmosphere to overcome a fear of speaking and making mistakes are desirable and form a contrast to the participants’ prior learning experiences, and it seems that participants need both academical and social support in their learning.